Productivity and spillover effect of merger and acquisitions in Malaysia - Aik, Nai Chiek; Hassan, Mohammad Kabir; Chowdury, Taufiq Hassan Shah; Ramadilli Mohd, Shamsher Mohamad (Emerald Group Publishing, 2015)
Purpose: This paper aims to examine the productivity and spillover effect of Malaysian horizontal merger and acquisition (M&A) activities in the long run. Design/methodology/approach: In terms of analytical tools, economic value added (EVA) and data envelopment analysis (DEA) are used. Findings: The results of this study reveal that M&As in the absence of antitrust laws could be driven by managerial self-interest to create market power instead of realizing synergistic gains. Also, in Malaysia, the non-merging rival firms have significantly higher productivity improvement than the control bidder firms, and therefore, this study has identified the spillover effect as a behavior of M&A reaction. Originality/value: This paper differs from previous studies in that it attempts not only to examine the real long-term gains of horizontal M&A activities in Malaysia but also the spillover effects of M&A activities on similar but non-merging firms.